Household Food Insecurity and its Association with Nutritional Status of Under Five Children in Indonesia - Hardi Firmansyah; Edy Marjuang Purba; Rasita Purba; Risti Rosmiati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Food insecurity remains a global challenge for public health, particularly among children. In Indonesia, where childhood malnutrition persists despite progress, regional disparities in food access, exacerbated by dietary shifts and income inequalities, underscore the importance of understanding how household food insecurity impacts child nutrition. Objective: to analyze the association between household food insecurity and nutritional status of Indonesian under-five children. Method: Data were collected from children participating in the 2014 Indonesia Family Life Survey (IFLS). The 17 items of the Food Frequency Questionnaire (FFQ) were used in the food consumption score analysis to assess food insecurity based on the World Food Program (WFP) concept. Height and weight were measured to determine z-scores of weight-for-lengths. A multinomial logistic regression model was used to test the hypothesis. Result: The study included 4,391 children aged 1-5 years. Multinomial logistic regression revealed that children from moderately and severely food-insecure households had significantly higher odds of being wasted, overweight, or obese compared to food-secure households. The analysis highlighted the dual burden of malnutrition, with food insecurity associated with both undernutrition and overnutrition. Conclusion: Household food insecurity is strongly linked to both undernutrition and overnutrition in Indonesian children, presenting a dual burden of malnutrition. Public health interventions should target improving food security and ensuring access to diverse, nutrient-rich diets to reduce malnutrition in vulnerable populations.